Characteristics And Risk Factors of Post-Vaccination Covid-19 on Indonesian Adults: A Cross-Sectional Study - Niaga, Karmenia Jessica Kurnia; Martin, Alfianto (Jurnal Ners, 2024)
The COVID-19 pandemic has prompted various countries to carry out vaccinations as an effort to limit its spread. Despite the distribution of vaccines, COVID-19 cases are still being reported. This study aims to identify the risk factors that influence the occurrence and severity of post-vaccination COVID-19 in Indonesian citizens and describe its characteristics. This descriptive study was conducted from January to March 2022 using cross-sectional research design. The study population comprised of Indonesian citizens who have received COVID-19 vaccines and were infected afterwards. Data were collected through online questionnaires. Participants were classified based on the number and types of vaccine received and severity of manifestation. Of 623 Indonesian citizens, 111 (18%) experienced post-vaccination COVID-19. Mild symptoms were found in 72% participants and 12% participants were asymptomatic. The most common manifestation was anosmia (72%), followed by fever (55%). The entire participants with moderate and severe symptoms received the inactivated virus vaccine. Severe manifestations were found in participants with overweight or obesity, diabetes, heart disease, and autoimmune disease. Third dose of vaccination was related to mild or no symptoms. Our study recommends an administration of additional doses especially for at-risk populations. Keywords: COVID-19, Vaccines, Clinical Manifestation, Indonesia, Comorbidity